Design and Verification of Multiphase Multilevel Traction Inverter - Patrik Resutík; Michal Praženica; Slavomír Kaščák (Applied Sciences)
The paper presents the practical design and implementation of a three-level neutral point clamped (TNPC) six-phase inverter rated at 100 kVA. The study initiates with prior work review, whereby most research work done earlier was mainly simulation-based. Based on the simulation results, this paper focuses on the practical aspects of inverter design, such as the development of a power board on an Insulated Metal Substrate, a gate driver board, an interconnect board, and the main control board. An inverter physical prototype has been built and tested at 500 V and 20 kW of output power. The SiC semiconductor technology is the base of the inverter, which represents the main merit of the work. Finally, high power density, compact design, and high efficiency are shown, which are major contributions of the paper. Tests performed proved that the designed converter was operating reliably and efficiently. While a simple Sinusoidal Pulse Width Modulation (SPWM) control algorithm has been implemented, the overall performance of the inverter showed great promise for higher-power applications. Compact and high-efficiency TNPC converters are developed for meeting increasing demands of advanced energy, automotive, and industrial applications.